Analisis dan Evaluasi Infrastruktur Jaringan di SMA Negeri 3 Tasikmalaya - Dardha, Muhamad Yusa; Ikhlas, Andri Nur; Dzulfikar, Helmy (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze and evaluate the computer network infrastructure at SMA Negeri 3 Tasikmalaya, which highly depends on an internet connection for school operational activities, such as Dapodik, Computer Based Test (CBT) exams, and e-Raport. Although the school has implemented a dual ISP architecture, allocating the Indibiz line for Administration and a 100 Mbps iForte line for teachers and students, users frequently experience network performance degradation or bottlenecks during peak hours. Furthermore, wireless signal coverage currently reaches only 60%, resulting in the emergence of blank spot areas. Network performance evaluation was conducted using Quality of Service (QoS) parameters based on TIPHON standards. The analysis results indicate that during peak hours, the throughput value falls into the